1997
DOI: 10.1007/bf02303802
|View full text |Cite
|
Sign up to set email alerts
|

Association between sucrase-isomaltase and p53 expression in colorectal cancer

Abstract: SI expression and p53 mutation are associated significantly in CRC. Although the mechanism underlying such an association in presently unknown, the association may define a subset of patients with a worse prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Schoeppner et al [48] found that weak expression of in 66 colon cancer patients was associated with a significantly better survival (log rank P= 0.021) than was high expression of galectin-3 within colon carcinomas. However, Lise et al [49] studied 182 Stage I-III colon and rectal carcinoma patients and did not find any association between intratumoral expression of galectin-3 and cancer-specific survival for either colon or rectal primary cancer. The data of Lise et al [49] demonstrate a trend between absence of galectin-3 expression and outcome that does not reach significance.…”
Section: Cell Adhesion and Recognition Molecules As Prognostic Markermentioning
confidence: 98%
See 3 more Smart Citations
“…Schoeppner et al [48] found that weak expression of in 66 colon cancer patients was associated with a significantly better survival (log rank P= 0.021) than was high expression of galectin-3 within colon carcinomas. However, Lise et al [49] studied 182 Stage I-III colon and rectal carcinoma patients and did not find any association between intratumoral expression of galectin-3 and cancer-specific survival for either colon or rectal primary cancer. The data of Lise et al [49] demonstrate a trend between absence of galectin-3 expression and outcome that does not reach significance.…”
Section: Cell Adhesion and Recognition Molecules As Prognostic Markermentioning
confidence: 98%
“…However, Lise et al [49] studied 182 Stage I-III colon and rectal carcinoma patients and did not find any association between intratumoral expression of galectin-3 and cancer-specific survival for either colon or rectal primary cancer. The data of Lise et al [49] demonstrate a trend between absence of galectin-3 expression and outcome that does not reach significance. These differences may be due to the smaller number of patients or to an interaction with other variables.…”
Section: Cell Adhesion and Recognition Molecules As Prognostic Markermentioning
confidence: 98%
See 2 more Smart Citations